Titanium Dioxide Nanoparticle-Based Interdigitated Electrodes: A Novel Current to Voltage DNA Biosensor Recognizes E. coli O157:H7 - Sh., Nadzirah; N., Azizah; Uda, Hashim; Subash C. B., Gopinath; Mohd, Kashif (Plos One Publishing, 2015)
Nanoparticle-mediated bio-sensing promoted the development of novel sensors in the front of medical diagnosis. In the present study, we have generated and examined the potential of titanium dioxide (TiO2) crystalline nanoparticles with aluminium interdigitated electrode biosensor to specifically detect single-stranded E.coli O157:H7 DNA. The performance of this novel DNA biosensor was measured the electrical current response using a picoammeter. The sensor surface was chemically functionalized with (3-aminopropyl) triethoxysilane (APTES) to provide contact between the organic and inorganic surfaces of a singlestranded DNA probe and TiO2 nanoparticles while maintaining the sensing system’s physical characteristics. The complement of the target DNA of E. coli O157:H7 to the carboxylate- probe DNA could be translated into electrical signals and confirmed by the increased conductivity in the current-to-voltage curves. The specificity experiments indicate that the biosensor can discriminate between the complementary sequences from the base-mismatched and the non-complementary sequences. After duplex formation, the complementary target sequence can be quantified over a wide range with a detection limit of 1.0 x 10- 13M. With target DNA from the lysed E. coli O157:H7, we could attain similar sensitivity. Stability of DNA immobilized surface was calculated with the relative standard deviation (4.6%), displayed the retaining with 99% of its original response current until 6 months. This high-performance interdigitated DNA biosensor with high sensitivity, stability and non-fouling on a novel sensing platform is suitable for a wide range of biomolecular interactive analyses.